Combined Effects of Aerobic Exercise and Diet on Lipids and Lipoproteins in Overweight and Obese Adults: A Meta-Analysis. (4th March 2012) - Kelley, George A.; Kelley, Kristi S.; Roberts, Susan; Haskell, William
Abstract : This study used the aggregate data meta-analytic approach to determine the combined effects of aerobic exercise and diet on lipids and lipoproteins in overweight and obese adults. Twelve studies representing 859 men and women (443 intervention, 416 control) were included. Using random-effects models, statistically significant, intervention minus control reductions were found for TC (−12.8 mg/dL, 95% CI, −19.9 to −5.7), TC : HDL-C (−0.5 mg/dL, 95% CI, −0.8 to −0.1), LDL-C (−6.8 mg/dL, 95% CI, −11.8 to −1.8), and TG (−13.1 mg/dL, 95% CI, −21.2 to −5.0) but not HDL-C (−0.4 mg/dL, 95% CI, −2.3 to 1.6). Results remained robust when adjusted for publication bias, deleting each study from the model once, and collapsing results for multiple groups from the same study into one effect size. These findings suggest that concurrent aerobic exercise and diet improve TC, LDL-C, TC : HDL-C, and TG, but not HDL-C, in overweight and obese adults.